Artificial Intelligence and Robotics in Modern Medicine: Current Trends, Challenges, and Future Possibilities (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
Artificial intelligence (AI) and robotics are transforming contemporary healthcare systems through rapid advancements in computational power, data analytics, and automation. The integration of AI into clinical practice has significantly improved disease diagnosis, treatment planning, and patient management. Simultaneously, robotics has enhanced surgical precision, rehabilitation, and hospital logistics. This paper explores the evolution of AI and robotic technologies in medicine, reviewing their present applications, challenges, and future trajectories. Emphasis is placed on diagnostic accuracy, personalized treatment, medical education, and ethical implications. Drawing upon recent open-access research, the study highlights how intelligent systems can augment human expertise rather than replace it, ensuring that innovation advances patient-centered and equitable healthcare.